Efeitos benéficos do extrato das cascas de noz pecã (Carya illinoensis) sobre parâmetros bioquímicos e comportamentais de camundongos expostos ao fumo passivo - Reckziegel, Patrícia (2011)
Smoking is the second major reason of death worldwide, amounting 5 millions of deaths annually. The adverse effects of cigarette smoking are not limited to active smokers, but also to passive smokers, which comprise one third of worldwide adult population. Cigarette smoking contain nicotine and other addiction related compounds, as well as components that can generate oxidative stress (OS), an unbalance between oxidants and antioxidants of the body, probably responsible for the pathogenesis of smoke-related disorders. The shells of pecan nut (Carya illinoensis) are an industrial byproduct of low cost and high antioxidant potential, whose tea is popularly used as treatment for drug and smoking intoxications, however without scientific validation. Therefore, the present study investigated the possible protection of pecan nut shells aqueous extract (AE) against abstinence behavioral parameters and OS biochemical parameters in animals exposed to passive cigarette smoke. Swiss mice received drinking water or AE (25g/L), ad libitum, in the place of water during one week before and during 3 weeks of cigarette smoke exposure (6, 10 and 14 cigarettes/day each week, respectively), which occurred in a modified incubator. The environmental concentration of carbon monoxide and total suspended particulate matter in the incubator were 130ppm and 188mg/m3, respectively. Fifteen hours after the last cigarette smoke exposure, the animals were evaluated in the open-field test and in the marble burning test. Twenty hours after the last cigarette smoke exposure, the animals were anesthetized and euthanized by exsanguination (cardiac puncture), with collection of blood and removal of brain for biochemical analysis. Data were analyzed by one or two-way ANOVA, followed by Duncan s test when necessary. The protocol of cigarette smoke exposure increased total concentration of carbon dioxide in blood and the hematocrit, which are indirect biochemical markers of cigarette smoke exposure, and reduced the body weight gain of animals without altering fluid intake. In the open-field test, animals exposed to passive smoke showed increase in locomotor and exploratory activities, self-cleaning time and fecal pellets number, as well as in the number of beads hidden in the marble burning test, than the controls. The animals that received AE did not develop these behavioral changes, which indicate anxiety, characteristic related to smoking abstinence. In this study, the involvement of smoking with oxidative damages described in the literature was confirmed by increasing cerebral and erythrocyte lipid peroxidation, increasing in erythrocyte catalase (CAT) activity and decreasing in plasma ascorbic acid. The pecan shells AE was able to protect the mice exposed to cigarette smoke of the lipid peroxidation and decrease of plasma ascorbic acid levels. CAT activity remained high in erythrocytes and increased in brain of animals exposed to cigarette smoke and that received AE, possible as a compensatory mechanism to eliminate excess of reactive oxygen species (ROS) induced by cigarette smoke. It is hypothesized that these biochemical results are in large part due the high antioxidant potential of AE, confirmed by in vitro assays of ABTS (2,2'-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid)) and DPPH (2,2- diphenyl-1-picrylhydrazyl) and by measuring of total phenolic compounds and condensed tannins levels. By Pearson correlation, were observed positive correlations between behavioral parameters evaluated and erythrocyte lipid peroxidation, confirming the involvement of anxiety and OS. The results presented here show the protective effect of pecan nut shells AE on anxiety-like sings of cigarette withdrawal and on oxidative damages and altered antioxidant defenses induced by passive cigarette smoke in mice. Moreover, the popular use of pecan nut shell extract against cigarette smoke was confirmed. It is believed that this industrial byproduct can be considered in the treatment of smoking, increasing the poor therapeutic armamentarium currently employed for this end. Further studies elucidating the components present in this extract, as well as neural mechanisms related to these results are needed.